1997
DOI: 10.1073/pnas.94.12.6490
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced closure of constitutively open γ-aminobutyric acid channels with mutated M2 domains

Abstract: Ligand-gated ion channels display a fundamental property-channels remain virtually closed at rest and open upon agonist binding. Here we show that substituting alanines for either of two amino acid residues (T314 or L317) in the M2 region of the ␥-aminobutyric acid (GABA) 1 subunit results in spontaneous channel opening in the absence of ligand. Surprisingly, for two single point mutants (T314A or L317A), application of very low concentrations of agonist partially suppressed this spontaneous current, while hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 35 publications
8
31
1
Order By: Relevance
“…1A). Weak agonist-induced signals were the result of elevated base-line fluorescence (data not shown), suggesting an increased level of background conductance, which has been reported for some leucine 9Ј mutations in other Cysloop receptors (13,20,(22)(23)(24)(25). The L9ЈF mutant retained a maximal response comparable with that of WT-XFP.…”
Section: Gain-of-function Gating Mutation Increasesmentioning
confidence: 66%
“…1A). Weak agonist-induced signals were the result of elevated base-line fluorescence (data not shown), suggesting an increased level of background conductance, which has been reported for some leucine 9Ј mutations in other Cysloop receptors (13,20,(22)(23)(24)(25). The L9ЈF mutant retained a maximal response comparable with that of WT-XFP.…”
Section: Gain-of-function Gating Mutation Increasesmentioning
confidence: 66%
“…Thus, several ligand-gated channels have been reported to open spontaneously when (relatively minor) mutations have been introduced into their structure. Some examples for homomeric channels are GABA receptors (Pan et al, 1997;Torres and Weiss, 2002), glycine ␣1 receptors (Dupre et al, 2007), nicotinic ␣7 receptors (Bertrand et al, 1997), and glutamate ␦2 receptors (Zuo et al, 1997). The approach is of course subject to the criticism that the open state of the mutated channel is surely not identical with that of the liganded channel.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using sitedirected mutagenesis and ultrastructural analysis have identified the second transmembrane domain (M2) as the pore-lining domain in the cys-loop receptors. Hydrophilic substitutions of the conserved leucine in the mid-point of the M2 domain dramatically influence channel gating kinetics, increase agonist sensitivity, and create spontaneous opening channels in several members of the cys-loop receptors [11][12][13][33][34][35][36][37][38][39] . Although earlier studies using cysteine accessibility test suggested that the gate is in the intracellular end of M2 [39,40] , it is now clear that the accessibility of these residues in the intracellular end of M2 in the absence of agonist is due to spontaneous opening of the M2 mutant channel [41] .…”
Section: Functional Domains Of the Cys-loop Receptorsmentioning
confidence: 99%